Quality of life of family caregivers of stroke patients: a systematic review of qualitative research - Chen, Hongyun; Makhdzir, Norafisyah; Loh, Wei Chao; Wang, Lining (Professional Medical Publications, 2025)
Objectives: Stroke imposes a substantial burden on individuals and families. The caregiving role for stroke survivors is often assumed by family members. This systematic review aimed to synthesize qualitative studies that explored the lived experiences of family caregivers of stroke patients, thereby determining the breadth and depth of qualitative evidence on their experiences. Methods: The review included studies published between February 2009 and February 2024, following the PRISMA guidelines for Systematic Reviews. The following databases were searched: PubMed, Web of Science, Scopus, MEDLINE, ScienceDirect, HINARI databases for qualitative research exploring the experiences, needs, and burdens experienced by caregivers of stroke patients. Results: Eleven studies were systematically reviewed, revealing three primary themes: the multifaceted burdens experienced by family caregivers of stroke patients and the positive aspects of caregiving, including identified needs and sources of support. Conclusion: Healthcare professionals should prioritize the psychological well-being and caregiving needs of stroke survivors’ caregivers. Comprehensive support, including psychological counseling and professional training, should be provided to enhance their caregiving abilities. Additionally, governments and healthcare institutions should offer family-centered support to ensure the quality of life for both patients and their caregivers.